Green binder system for taphole clays: A potential for glycerine and phenolic resin - I.J-P. Cameron; A.M. Garbers-Craig (Open Ceramics, 2025)
Recent advancements in taphole clay binder development have focused on replacing toxic coal tar/pitch, which contains polycyclic aromatic hydrocarbons (PAH), with greener alternatives. In this study, three different taphole clays were prepared in the laboratory using different binder systems which include phenolic resin: 1) coal tar, 2) glycerine, and 3) petroleum waxy oil. The clays were evaluated and compared to the conventional coal tar and phenolic resin-containing clay used in platinum smelters. The evaluation methods employed included workability and extrusion pressure ageing, hardenability, strength development, and high-temperature properties, which comprised cold crushing strength after ageing at 200 °C, carbon yield, volatile organic compound concentration and apparent porosity. The results indicated that the preferred binder to replace coal tar was glycerine, as this clay retained both its plasticity and hardenability during ageing, while also attaining comparative strength development and high-temperature properties to those of the reference clay containing coal tar.